Water-based inorganic fireproof energy-storage luminescent coating as well as preparation method and application thereof
By introducing modified rare earth aluminate luminescent materials into inorganic silicate luminescent coatings, the problems of poor storage properties of the coating and rough and easy cracking surface after film formation are solved, and water-based inorganic fire-resistant energy-saving luminescent coatings with high stability and good crack resistance are achieved.
Patent Information
- Application Number
- CN202510118436.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-22
AI Technical Summary
The existing inorganic silicate-based luminescent coatings have problems such as poor storage, rough surface after film formation, and easy cracking.
The water-based inorganic fire-resistant energy-saving luminescent coating is used to combine the modified rare earth aluminate luminescent material with the inorganic silicate system to improve the storage stability and film formation stability of the coating, and increase the surface smoothness and crack resistance.
It has achieved good storage stability and film formation stability of water-based inorganic fire-resistant energy-saving luminescent coatings. The surface after film formation is smooth and crack resistance is good. It also has A-level fireproof and AQ1 safety level smoke-producing toxicity hazard classification.
Smart Images

Figure BDA0005258365300000141 
Figure BDA0005258365300000142 
Figure BDA0005258365300000151
Abstract
Description
Technical Field
[0001] The invention belongs to the field of building materials, and specifically relates to a water-based inorganic fireproof energy storage luminous paint and a preparation method and application thereof. Background Art
[0002] In the process of building transportation channels, tunnels have been favored by planners and builders for their convenience and low cost, and undersea tunnels and high-speed tunnels have also developed rapidly. Among them, tunnels with large scale and long mileage, especially undersea tunnels, are relatively closed in structure and have large traffic flow. Once a fire occurs in the tunnel, it is quite difficult to extinguish the fire. Therefore, it is very important to improve the fire prevention capacity of tunnels.
[0003] Generally, the fireproof ability of the tunnel is improved by brushing fireproof coating on the walls of the tunnel. However, the main raw materials of traditional organic architectural coatings come from natural resources such as coal, oil, and natural gas. Not only will a large amount of by-products, volatile solvents, and residual monomers be produced during processing, which will not only cause environmental pollution but also waste a lot of resources and energy; and these polymer materials are all petrochemical products, which are all flammable products. When a fire occurs, a large amount of toxic smoke will be produced (it has been proved that 80% of deaths in fires are caused by smoke suffocation), which does not meet the safety acceptance requirements for fire smoke toxicity. At the same time, this type of latex paint with petrochemical products as raw materials is easy to release benzene and VOC volatile organic compounds, and its environmental protection and safety performance does not meet the requirements of green and healthy development. In addition, when a fire occurs, it often causes a power outage in the tunnel lighting circuit. The longer the tunnel, the more corresponding lighting facilities are equipped, which increases energy consumption. The energy storage luminous coating can deal with these problems well. It can absorb visible light to store light energy, and then convert it into visible light emission through excitation, which plays the role of emergency lighting; at the same time, the energy storage luminous coating can also be used alternately with the lighting facilities in the tunnel to reduce energy consumption.
[0004] Therefore, it is urgent to find a coating with good fire resistance, safety, environmental protection and good luminous performance to meet the above needs. Compared with these defects of traditional organic coatings, inorganic silicate coatings have good air permeability, anti-pollution and non-flammability up to Class A, and excellent comprehensive environmental performance. However, due to the characteristics of inorganic silicate coatings themselves, they easily react with multivalent metal ions in the system and luminescent materials such as rare earth aluminate luminescent materials to form insoluble silicates, which leads to problems such as unstable storage performance, rough surface after film formation, and easy cracking of inorganic silicate luminescent coatings. Summary of the invention
[0005] The purpose of the present invention is to provide a water-based inorganic fire-retardant energy storage luminous coating and its preparation method and application in view of the problems of poor storage, rough surface after film formation and easy cracking of existing inorganic silicate luminous coatings.
[0006] In a first aspect, the present invention provides a water-based inorganic fire-retardant energy-storage luminous coating.
[0007] Specifically, based on the total mass of the water-based inorganic fire-proof energy-storage luminescent coating, the water-based inorganic fire-proof energy-storage luminescent coating contains 18.0-50.0wt% of water, 15.0-35.0wt% of inorganic silicate, 3.0-10.0wt% of inorganic hybrid resin, 25.0-45.0wt% of modified rare earth aluminate luminescent material, 0.1-0.6wt% of cellulose, and 0.2-3.6wt% of auxiliary agent; the modified rare earth aluminate luminescent material is obtained by modifying the unmodified rare earth aluminate luminescent material with alkynyl compounds, vinyl-terminated polymethylsiloxane, and alkylbenzene sulfonate.
[0008] In a preferred embodiment, the mass ratio of the unmodified rare earth aluminate luminescent material to the acetylenic compound, vinyl-terminated polymethylsiloxane, and alkylbenzene sulfonate is 1:(0.002-0.004):(0.003-0.006):(0.003-0.006).
[0009] In a preferred embodiment, the unmodified rare earth aluminate luminescent material is selected from at least one of strontium aluminate, barium aluminate, calcium aluminate, europium aluminate and manganese aluminate.
[0010] In a preferred embodiment, the alkynyl compound is selected from at least one of acetylene, 1-propyne, 2-propyne, 1-butyne, 2-butyne, 1-pentyne, 2-pentyne, and 3-methyl-1-butyne.
[0011] In a preferred embodiment, the number average molecular weight of the vinyl-terminated polymethylsiloxane is 200 to 400 g / mol.
[0012] In a preferred embodiment, the alkylbenzene sulfonate is selected from at least one of sodium dodecylbenzene sulfonate, potassium dodecylbenzene sulfonate, calcium dodecylbenzene sulfonate and triethanolamine dodecylbenzene sulfonate.
[0013] In a preferred embodiment, the modification reaction conditions include: temperature of 120-200° C. and time of 3-5 h.
[0014] In a preferred embodiment, the modification reaction is carried out in the presence of a solvent.
[0015] In a preferred embodiment, the particle size of the modified rare earth aluminate luminescent material is 25 to 75 μm.
[0016] In a preferred embodiment, the inorganic silicate is selected from at least one of potassium silicate, lithium silicate, sodium silicate and silica sol.
[0017] In a preferred embodiment, the auxiliary agent is selected from at least one of a defoaming agent, a wetting and dispersing agent, an anti-mildew and anti-algae agent, and a thickener.
[0018] In a preferred embodiment, based on the total mass of the water-based inorganic fire-retardant energy-storage luminous coating, the content of the defoaming agent is 0.2-0.8wt%, the content of the wetting and dispersing agent is 0.3-1.0wt%, the content of the mildew and algae preventer is 0.2-1.0wt%, and the content of the thickener is 0.2-0.8wt%.
[0019] In a preferred embodiment, the wetting and dispersing agent is selected from at least one of amines, phosphates, carboxylates, polyacid homopolymers, and polyacid copolymers.
[0020] In a preferred embodiment, the mildew and algae preventer is selected from at least one of OIT, DCOIT, MIT, IPBC and ZnP.
[0021] In a preferred embodiment, the thickener is selected from at least one of a polyurethane thickener, an alkali swelling thickener, and a bentonite thickener.
[0022] In the second aspect, the present invention provides a method for preparing the above-mentioned water-based inorganic fire-retardant energy storage luminous coating, which comprises: mixing water, inorganic silicate, inorganic hybrid resin, modified rare earth aluminate luminescent material, cellulose and additives in proportion to obtain a water-based inorganic fire-retardant energy storage luminous coating.
[0023] In a third aspect, the present invention provides the application of the above-mentioned water-based inorganic fire-retardant energy-storage luminous coating in tunnels and other building materials.
[0024] The key to the present invention is to introduce the rare earth aluminate luminescent material modified by a specific method into the inorganic silicate system, which not only has good compatibility with the inorganic silicate, giving the inorganic silicate coating system good luminescent properties, but also can effectively improve the storage stability and film-forming stability of the inorganic silicate system, so that the surface of the inorganic silicate luminescent coating is smooth after film formation and has good crack resistance. In summary, the water-based inorganic fireproof energy storage luminescent coating provided by the present invention not only has good storage stability and film-forming stability, the surface is smooth and has good crack resistance after film formation, but also can reach Class A fire protection, and the smoke toxicity hazard classification can reach AQ1 safety level. It is a coating with good fire resistance, safety, environmental protection and good luminescent properties, which can well meet the application needs of tunnels. DETAILED DESCRIPTION
[0025] The water-based inorganic fireproof energy storage luminous paint provided by the invention contains water, inorganic silicate, inorganic hybrid resin, modified rare earth aluminate luminous material, cellulose and auxiliary agent. Based on the total mass of the water-based inorganic fire-proof energy-storage luminous coating, the water content is 18.0-50.0wt%, such as 18.0wt%, 20.0wt%, 22.0wt%, 25.0wt%, 30.0wt%, 35.0wt%, 40.0wt%, 45.0wt%, 50.0wt% or any value therebetween; the inorganic silicate content is 15.0-35.0wt%, such as 15.0wt%, 18.0wt%, 20.0wt%, 22.0wt%, 25.0wt%, 28.0wt%, 30.0wt%, 35.0wt% or any value therebetween; the inorganic hybrid resin content is 3.0-10.0wt%, such as 3.0wt%, 4.0wt%, 5.0wt%, 6.0wt%, 7.0wt%, 8.0wt%, 9. 0wt%, 10.0wt% or any value therebetween; the content of the modified rare earth aluminate luminescent material is 25.0-45.0wt%, such as 25.0wt%, 28.0wt%, 30.0wt%, 32.0wt%, 35.0wt%, 38.0wt%, 40.0wt%, 45.0wt% or any value therebetween; the content of the cellulose is 0.1-0.6wt%, such as 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt% or any value therebetween; the content of the auxiliary agent is 0.2-3.6wt%, such as 0.2wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.6wt% or any value therebetween.
[0026] In the present invention, based on the total mass of the water-based inorganic fire-retardant energy-storage luminous coating, the water content is preferably 18.0-40.0wt%, such as 18.0wt%, 20.0wt%, 22.0wt%, 25.0wt%, 30.0wt%, 35.0wt%, 40.0wt%; the content of the inorganic silicate is preferably 15.0-32.0wt%, such as 15.0wt%, 18.0wt%, 20.0wt%, 22.0wt%, 25.0wt%, 28.0wt%, 30.0wt%, 32.0wt% or any value therebetween; the content of the inorganic hybrid resin is preferably 3.0-8.0wt%, such as 3.0wt%, 4.0wt%, 5.0wt%, 6.0wt%, 7.0wt%. t%, 8.0wt% or any value therebetween; the content of the modified rare earth aluminate luminescent material is preferably 30.0-40.0wt%, such as 28.0wt%, 30.0wt%, 32.0wt%, 35.0wt%, 38.0wt%, 40.0wt% or any value therebetween; the content of the cellulose is preferably 0.1-0.5wt%, such as 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt% or any value therebetween; the content of the auxiliary agent is preferably 0.2-3.1wt%, such as 0.2wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.1wt% or any value therebetween.
[0027] In the present invention, the modified rare earth aluminate luminescent material is obtained by modifying an unmodified rare earth aluminate luminescent material with an alkynyl compound, vinyl-terminated polymethylsiloxane and alkylbenzene sulfonate.
[0028] Furthermore, the mass ratio of the unmodified rare earth aluminate luminescent material to the acetylenic compound, vinyl-terminated polymethylsiloxane, and alkylbenzene sulfonate is preferably 1:(0.002-0.004):(0.003-0.006):(0.003-0.006). Based on the mass of the unmodified rare earth aluminate luminescent material as 1 part by weight, the amount of the alkynyl compound is preferably 0.002 to 0.004 parts by weight, such as 0.002, 0.0025, 0.003, 0.0035, 0.004 parts by weight or any value therebetween; the amount of the vinyl-terminated polymethylsiloxane is preferably 0.003 to 0.006 parts by weight, such as 0.003, 0.0035, 0.004, 0.0045, 0.005, 0.0055, 0.006 parts by weight or any value therebetween; the amount of the alkylbenzene sulfonate is preferably 0.003 to 0.006 parts by weight, such as 0.003, 0.0035, 0.004, 0.0045, 0.005, 0.0055, 0.006 parts by weight or any value therebetween. By controlling the mass ratio of the unmodified rare earth aluminate luminescent material to the acetylenic compound, vinyl-terminated polymethylsiloxane and alkylbenzene sulfonate within the above-mentioned preferred range, the free metal ion content in the coating system containing the modified rare earth aluminate luminescent material can be further reduced, while the polarity and friction of the luminescent material can be improved, so that the powder stacking is more compact, the oil absorption value is further reduced, and the stability of the luminescent material in the system is greatly improved, the oil absorption is reduced and the anti-cracking effect of the coating is improved.
[0029] Furthermore, the conditions of the modification reaction may include: the temperature is preferably 120-200°C, such as 120°C, 140°C, 150°C, 180°C, 200°C or any value therebetween; the time is preferably 3-5h, such as 3h, 4h, 5h, 6h or any value therebetween.
[0030] Further, the modification reaction is carried out in the presence of a solvent. The solvent is preferably water. The mass ratio of the unmodified rare earth aluminate luminescent material to the solvent is preferably 1:(2.5-6). Based on the mass of the unmodified rare earth aluminate luminescent material as 1 part by weight, the amount of the solvent is preferably 2.5-6 parts by weight, such as 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6 parts by weight or any value therebetween.
[0031] In a specific embodiment, the preparation steps of the modified rare earth aluminate luminescent material are as follows: unmodified rare earth aluminate luminescent material, alkynyl compound, vinyl terminated polymethylsiloxane, and alkylbenzene sulfonate are mixed evenly in water and then allowed to stand for 24 to 48 hours, then filtered and dried to obtain an intermediate product, and then the obtained intermediate product is subjected to a modification reaction at 120 to 200° C. for 3 to 5 hours to obtain the modified rare earth aluminate luminescent material. The mixing order of the unmodified rare earth aluminate luminescent material, alkynyl compound, vinyl terminated polymethylsiloxane, alkylbenzene sulfonate and water is not specifically limited, and they can be added and mixed at the same time, or some raw materials can be mixed with water first and then the remaining raw materials are added and mixed. It is preferred that the unmodified rare earth aluminate luminescent material is first added and mixed with water, and then the alkynyl compound, vinyl terminated polymethylsiloxane, and alkylbenzene sulfonate are added and mixed.
[0032] In the present invention, specific examples of the unmodified rare earth aluminate luminescent material include, but are not limited to, at least one of strontium aluminate, barium aluminate, calcium aluminate, europium aluminate, and manganese aluminate.
[0033] In the present invention, specific examples of the alkynyl compound include, but are not limited to, at least one of acetylene, 1-propyne, 2-propyne, 1-butyne, 2-butyne, 1-pentyne, 2-pentyne, and 3-methyl-1-butyne, more preferably 3-methyl-1-butyne.
[0034] In the present invention, the number average molecular weight of the vinyl terminated polymethylsiloxane is preferably 200-400 g / mol, such as 200 g / mol, 230 g / mol, 260 g / mol, 280 g / mol, 300 g / mol, 350 g / mol, 400 g / mol or any value therebetween.
[0035] In the present invention, specific examples of the alkylbenzene sulfonate include, but are not limited to, at least one of sodium dodecylbenzene sulfonate, potassium dodecylbenzene sulfonate, calcium dodecylbenzene sulfonate, and triethanolamine dodecylbenzene sulfonate.
[0036] In the present invention, the particle size of the modified rare earth aluminate luminescent material is preferably 25 to 75 μm, such as 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm or any value therebetween. The particle size of the modified rare earth aluminate luminescent material is controlled within the above preferred range, firstly, to ensure good luminescent performance, and secondly, to be better compatible with inorganic silicates, thereby improving the smoothness and crack resistance of the surface of the coating after film formation.
[0037] In the present invention, specific examples of the inorganic silicate include, but are not limited to, at least one of potassium silicate, lithium silicate, sodium silicate, and silica sol.
[0038] In the present invention, specific examples of the inorganic hybrid resin include but are not limited to: at least one of ES1805 and ES1806 of Aorun Chemical, and KS49, KS56, KS49-2 and KS49-3 of Xipusen New Materials.
[0039] In the present invention, specific examples of the cellulose include, but are not limited to, at least one of carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose.
[0040] In the present invention, the auxiliary agent is preferably at least one of a self-defoaming agent, a wetting and dispersing agent, an anti-mildew and anti-algae agent, and a thickener.
[0041] In the present invention, based on the total mass of the water-based inorganic fire-retardant energy-storage luminous coating, the content of the defoamer is preferably 0.2-0.8wt%, such as 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt% or any value therebetween; the content of the wetting and dispersing agent is preferably 0.3-1.0wt%, such as 0.3wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1.0wt% or any value therebetween; the content of the mildew and algae preventer is preferably 0.2-1.0wt%, such as 0.2wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1.0wt% or any value therebetween; the content of the thickener is preferably 0.2-0.8wt%, such as 0.2wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.8wt% or any value therebetween.
[0042] Furthermore, based on the total mass of the water-based inorganic fire-retardant energy-storage luminous coating, the content of the defoamer is preferably 0.2-0.7wt%, such as 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt% or any value therebetween; the content of the wetting and dispersing agent is preferably 0.5-1.0wt%, such as 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0 wt% or any value therebetween; the content of the mildew and algae preventer is preferably 0.2-0.8wt%, such as 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt% or any value therebetween; the content of the thickener is preferably 0.2-0.6wt%, such as 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt% or any value therebetween.
[0043] In the present invention, the wetting and dispersing agent is preferably at least one selected from amines, phosphates, carboxylates, polyacid homopolymers, and polyacid copolymers.
[0044] In the present invention, specific examples of the mildew and algae preventer include, but are not limited to: at least one of OIT (2-octyl-4-isothiazoline-3-one), DCOIT (4,5-dichloro-N-octyl-4-isothiazoline-3-one), MIT (2-methyl-4-isothiazoline-3-one), IPBC (3-iodo-2-propargyl butylcarbamate), and ZnP.
[0045] In the present invention, specific examples of the thickener include, but are not limited to: at least one of a polyurethane thickener, an alkali swelling thickener, and a bentonite thickener.
[0046] The preparation method of the water-based inorganic fireproof energy storage luminescent coating provided by the present invention comprises: mixing water, inorganic silicate, inorganic hybrid resin, luminescent material, cellulose, and auxiliary agent according to a proportion to obtain the water-based inorganic fireproof energy storage luminescent coating. The mixing order of the water, inorganic silicate, inorganic hybrid resin, modified rare earth aluminate luminescent material, cellulose, and auxiliary agent is not specifically limited, and they can be added and mixed at the same time, or several of the raw materials can be mixed first and then the remaining raw materials are added and mixed continuously.
[0047] In a specific embodiment, the preparation method comprises the following steps: first, stirring and mixing cellulose and water until the cellulose is completely swollen, and the stirring time t1 can be 15 to 25 minutes, such as 15 minutes, 18 minutes, 20 minutes, 22 minutes, 25 minutes or any value therebetween; then, adding the modified rare earth aluminate luminescent material and continuing to stir and mix, the stirring time t2 can be 10 to 20 minutes, such as 10 minutes, 12 minutes, 15 minutes, 18 minutes, 20 minutes or any value therebetween; then, adding the inorganic silicate, the inorganic hybrid resin and the auxiliary agent and continuing to stir and mix, the stirring time t3 can be 10 to 20 minutes, such as 10 minutes, 12 minutes, 15 minutes, 18 minutes, 20 minutes or any value therebetween; and the resulting mixture is a water-based inorganic fire-retardant energy storage luminescent coating.
[0048] In a specific embodiment, the preparation method comprises the following steps: firstly stirring and mixing cellulose, defoaming agent, wetting and dispersing agent with water until the cellulose is completely swollen, the stirring time t1 can be 15 to 25 minutes, such as 15 minutes, 18 minutes, 20 minutes, 22 minutes, 25 minutes or any value therebetween, then adding modified rare earth aluminate luminescent material and continuing stirring and mixing, the stirring time t2 can be 10 to 20 minutes, such as 10 minutes, 12 minutes, 15 minutes, 18 minutes, 20 minutes or any value therebetween, then adding inorganic silicate, inorganic hybrid resin, mildew and algae proof agent and thickener and continuing stirring and mixing, the stirring time t3 can be 10 to 20 minutes, such as 10 minutes, 12 minutes, 15 minutes, 18 minutes, 20 minutes or any value therebetween, and the resulting mixture is a water-based inorganic fire-retardant energy storage luminescent coating.
[0049] The present invention will be described in detail below through specific embodiments.
[0050] The sources of the raw materials involved in the following examples and comparative examples are as follows: unmodified strontium aluminate, purchased from Zhejiang Minghui Luminescent Technology Co., Ltd., model MHB-4C, particle size 45 ~ 55μm; unmodified strontium aluminate, purchased from Zhejiang Minghui Luminescent Technology Co., Ltd., model MHB-3C, particle size 55 ~ 75μm; unmodified strontium aluminate, purchased from Zhejiang Minghui Luminescent Technology Co., Ltd., model MHB-5D, particle size 25 ~ 35μm; vinyl terminated polymethylsiloxane, purchased from Hubei Zhonglong Kangsheng Fine Chemical Co., Ltd., brand MP5000, number average molecular weight 260.55g / mol; silica sol, purchased from Shanghai Aorun Chemical Co., Ltd., brand S308; modified silica sol impurities The resin was purchased from Aorun Chemical with the brand names ES1805 and ES1806; the inorganic modified silicone resin was purchased from Xipusen New Materials Co., Ltd. with the brand name KS56; the water-based inorganic zinc-rich resin was purchased from Xipusen New Materials Co., Ltd. with the brand name KS49; the silicone defoamer was purchased from Blackburn with the brand name CF1829; the hydrophobic modified ammonium salt dispersant was purchased from Nouryon Chemical with the brand name Alcosperse747; the wetting agent was purchased from Nouryon Chemical with the brand names Ethylan1005, Ethylan324 and Ethylan1008; the polyurethane thickener was purchased from Dow Chemical with the brand names RM-8W, RM-12W and RM-2020NPR.
[0051] Preparation Example 1 Preparation of modified rare earth aluminate luminescent material A1
[0052] 10 parts by weight of unmodified strontium aluminate (MHB-4C) were added into 40 parts by weight of water and mixed evenly, and then 0.03 parts by weight of 3-methyl-1-butyne, 0.05 parts by weight of vinyl-terminated polymethylsiloxane MP5000 and 0.04 parts by weight of sodium dodecylbenzene sulfonate were added, mixed evenly and allowed to stand for 36 hours, and then filtered and dried to obtain an intermediate product, and the intermediate product was kept warm at 160°C for 4 hours to obtain a modified rare earth aluminate luminescent material A1 with a particle size of 45 to 55 μm.
[0053] Preparation Example 2 Preparation of modified rare earth aluminate luminescent material A2
[0054] 10 parts by weight of unmodified strontium aluminate (MHB-3C) are added to 40 parts by weight of water and mixed evenly, and then 0.02 parts by weight of 1-butyne, 0.03 parts by weight of vinyl-terminated polymethylsiloxane MP5000 and 0.03 parts by weight of potassium dodecylbenzenesulfonate are added, mixed evenly and allowed to stand for 36 hours, and then filtered and dried to obtain an intermediate product, and the intermediate product is kept warm at 140°C for 5 hours to obtain a modified rare earth aluminate luminescent material A2 with a particle size of 55 to 75 μm.
[0055] Preparation Example 3 Preparation of modified rare earth aluminate luminescent material A3
[0056] 10 parts by weight of unmodified strontium aluminate (MHB-5D) are added to 40 parts by weight of water and mixed evenly, and then 0.04 parts by weight of 1-pentyne, 0.06 parts by weight of vinyl-terminated polymethylsiloxane MP5000 and 0.06 parts by weight of sodium dodecylbenzene sulfonate are added, mixed evenly and allowed to stand for 36 hours, and then filtered and dried to obtain an intermediate product, and the intermediate product is kept warm for reaction at 180°C for 3 hours to obtain a modified rare earth aluminate luminescent material A3 with a particle size of 25 to 35 μm.
[0057] Preparation Example 4 Preparation of modified rare earth aluminate luminescent material A4
[0058] A modified rare earth aluminate luminescent material was prepared according to the method of Preparation Example 1, except that 0.005 weight parts of 3-methyl-1-butyne, 0.08 weight parts of vinyl-terminated polymethylsiloxane MP5000, and 0.1 weight parts of sodium dodecylbenzene sulfonate were added, and the other conditions were the same as those in Preparation Example 1, thereby obtaining a modified rare earth aluminate luminescent material A4 with a particle size of 45 to 55 μm.
[0059] Preparation Example 5 Preparation of modified rare earth aluminate luminescent material A5
[0060] The modified rare earth aluminate luminescent material was prepared according to the method of Preparation Example 1, except that 0.06 weight parts of 3-methyl-1-butyne, 0.01 weight parts of vinyl-terminated polymethylsiloxane MP5000, and 0.01 weight parts of sodium dodecylbenzene sulfonate were added, and the other conditions were the same as those in Preparation Example 1, thereby obtaining a modified rare earth aluminate luminescent material A5 with a particle size of 45 to 55 μm.
[0061] Comparative Preparation Example 1 Preparation of Reference Modified Rare Earth Aluminate Luminescent Material DA1
[0062] A reference modified rare earth aluminate luminescent material was prepared according to the method of Preparation Example 1, except that the same weight portion of 3-methyl-1-butyne was used instead of vinyl-terminated polymethylsiloxane, and the other conditions were the same as those in Preparation Example 1, thereby obtaining a reference modified rare earth aluminate luminescent material DA1 with a particle size of 45 to 55 μm.
[0063] Comparative Preparation Example 2 Preparation of Reference Modified Rare Earth Aluminate Luminescent Material DA2
[0064] A reference modified rare earth aluminate luminescent material was prepared according to the method of Preparation Example 1, except that the same weight portion of vinyl-terminated polymethylsiloxane was used instead of 3-methyl-1-butyne, and the other conditions were the same as those in Preparation Example 1, thereby obtaining a reference modified rare earth aluminate luminescent material DA2 with a particle size of 45 to 55 μm.
[0065] Example 1 Preparation of water-based inorganic fire-proof energy storage luminous coating
[0066] The raw materials include: 37.7wt% water, 20.0wt% inorganic silicate, 5.0wt% inorganic hybrid resin, 35.0wt% modified rare earth aluminate luminescent material A1 (particle size is 45-55μm), 0.3wt% cellulose, 0.3wt% defoamer, 0.7wt% wetting dispersant, 0.5wt% mildew and algae preventer, 0.5wt% thickener. The inorganic silicate is silica sol S308; the inorganic hybrid resin is modified silica sol hybrid resin ES1805; the cellulose is hydroxymethyl cellulose; the defoamer is organic silicon defoamer CF1829; the wetting dispersant is hydrophobically modified ammonium salt dispersant Alcosperse747 and wetting agent Ethylan1005; the mildew and algae preventer is OIT; and the thickener is polyurethane thickener RM-8W.
[0067] Preparation steps: first stir and mix cellulose, defoaming agent, wetting dispersant and water until the cellulose is completely swollen, the stirring time t1 is 20 minutes, then add the luminescent material and continue to stir and mix, the stirring time t2 is 15 minutes, and then add inorganic silicate, inorganic hybrid resin, mildew and algae inhibitor, thickener and continue to stir and mix, the stirring time t3 is 15 minutes, and the resulting mixture is a water-based inorganic fire-retardant energy storage luminous paint.
[0068] Example 2 Preparation of water-based inorganic fire-proof energy storage luminous coating
[0069] The raw materials include: 37.7wt% water, 20.0wt% inorganic silicate, 5.0wt% inorganic hybrid resin, 35.0wt% luminescent material is modified rare earth aluminate luminescent material A2 (particle size is 55-75μm), 0.3wt% cellulose, 0.3wt% defoamer, 0.7wt% wetting dispersant, 0.5wt% mildew and algae preventer, 0.5wt% thickener. The inorganic silicate is potassium silicate; the inorganic hybrid resin is modified silica sol hybrid resin ES1806; the cellulose is hydroxyethyl cellulose; the defoamer is organic silicon defoamer CF1829; the wetting dispersant is hydrophobically modified ammonium salt dispersant Alcosperse747 and wetting agent Ethylan324; the mildew and algae preventer is DCOIT; the thickener is polyurethane thickener RM-12W.
[0070] Preparation steps: The same as the preparation method in Example 1, thereby preparing a water-based inorganic fire-retardant energy-storage luminous coating.
[0071] Example 3 Preparation of water-based inorganic fire-proof energy storage luminous coating
[0072] The raw materials include: 42.7wt% water, 20.0wt% inorganic silicate, 5.0wt% inorganic hybrid resin, 30.0wt% modified rare earth aluminate luminescent material A3 (particle size is 25-35μm), 0.3wt% cellulose, 0.3wt% defoamer, 0.7wt% wetting dispersant, 0.5wt% mildew and algae preventer, 0.5wt% thickener. The inorganic silicate is sodium silicate; the inorganic hybrid resin is inorganic modified silicone resin KS56; the cellulose is methyl cellulose; the defoamer is organic silicon defoamer CF1829; the wetting dispersant is hydrophobically modified ammonium salt dispersant Alcosperse747 and wetting agent Ethylan1008; the mildew and algae preventer is ZnP; and the thickener is polyurethane thickener RM-2020NPR.
[0073] Preparation steps: The same as the preparation method in Example 1, thereby preparing a water-based inorganic fire-retardant energy-storage luminous coating.
[0074] Example 4 Preparation of water-based inorganic fire-proof energy storage luminous coating
[0075] The raw materials include: 35.9wt% water, 15.0wt% inorganic silicate, 7.0wt% inorganic hybrid resin, 40.0wt% modified rare earth aluminate luminescent material A1 (particle size is 45-55μm), 0.1wt% cellulose, 0.3wt% defoamer, 0.7wt% wetting dispersant, 0.5wt% mildew and algae preventer, 0.5wt% thickener. The inorganic silicate is silica sol S308; the inorganic hybrid resin is water-based inorganic zinc-rich resin KS49; the cellulose is hydroxymethyl cellulose; the defoamer is organic silicon defoamer CF1829; the wetting dispersant is hydrophobically modified ammonium salt dispersant Alcosperse747 and wetting agent Ethylan1005; the mildew and algae preventer is OIT; and the thickener is polyurethane thickener RM-8W.
[0076] Preparation steps: The same as the preparation method in Example 1, thereby preparing a water-based inorganic fire-retardant energy-storage luminous coating.
[0077] Example 5 Preparation of water-based inorganic fire-proof energy storage luminous coating
[0078] The raw materials include: 34.5wt% water, 30.0wt% inorganic silicate, 3.0wt% inorganic hybrid resin, 30.0wt% modified rare earth aluminate luminescent material A1 (particle size of 45-55μm), 0.5wt% cellulose, 0.3wt% defoamer, 0.7wt% wetting dispersant, 0.5wt% mildew and algae preventer, and 0.5wt% thickener. The inorganic silicate is silica sol S308; the inorganic hybrid resin modified silica sol hybrid resin ES1805; the cellulose is hydroxymethyl cellulose; the defoamer is the organosilicon defoamer CF1829; the wetting dispersant is the hydrophobically modified ammonium salt dispersant Alcosperse747 and the wetting agent Ethylan1005; the mildew and algae preventer is OIT; and the thickener is the polyurethane thickener RM-8W.
[0079] Preparation steps: The same as the preparation method in Example 1, thereby preparing a water-based inorganic fire-retardant energy-storage luminous coating.
[0080] Example 6 Preparation of water-based inorganic fire-proof energy storage luminous coating
[0081] The raw materials include: the same as the raw materials in Example 1, except that the luminescent material is a modified rare earth aluminate luminescent material A4.
[0082] Preparation steps: The same as the preparation method in Example 1, thereby preparing a water-based inorganic fire-retardant energy-storage luminous coating.
[0083] Example 7 Preparation of water-based inorganic fire-proof energy storage luminous coating
[0084] The raw materials include: the same as the raw materials in Example 1, except that the luminescent material is a modified rare earth aluminate luminescent material A5.
[0085] Preparation steps: The same as the preparation method in Example 1, thereby preparing a water-based inorganic fire-retardant energy-storage luminous coating.
[0086] Comparative Example 1 Preparation of Reference Water-Based Inorganic Fire-Resistant Energy-Storage Luminous Coating
[0087] The raw materials include: 37.7kg water, 20.0kg inorganic silicate, 5.0kg inorganic hybrid resin, 35.0kg unmodified strontium aluminate luminescent material (MHB-4C), 0.3kg cellulose, 0.3kg defoamer, 0.7kg wetting and dispersing agent, 0.5kg mildew and algae preventer, and 0.5kg thickener. The inorganic silicate is silica sol S308; the inorganic hybrid resin modified silica sol hybrid resin ES1805; the cellulose is hydroxymethyl cellulose; the defoamer is the organosilicon defoamer CF1829; the wetting and dispersing agent is the hydrophobically modified ammonium salt dispersant Alcosperse747 and the wetting agent Ethylan1005; the mildew and algae preventer is OIT; and the thickener is the polyurethane thickener RM-8W.
[0088] Preparation steps: The same as the preparation method in Example 1, thereby preparing a reference water-based inorganic fire-retardant energy-storage luminous coating.
[0089] Comparative Example 2 Preparation of Reference Water-Based Inorganic Fire-Resistant Energy Storage Luminous Coating
[0090] The raw materials include: 27.7kg water, 20.0kg inorganic silicate, 5.0kg inorganic hybrid resin, 45.0kg modified rare earth aluminate luminescent material A1 (particle size is 45-55μm), 0.3kg cellulose, 0.3kg defoamer, 0.7kg wetting dispersant, 0.5kg mildew and algae preventer, 0.5kg thickener. The inorganic silicate is silica sol S308; the inorganic hybrid resin modified silica sol hybrid resin ES1805; the cellulose is hydroxymethyl cellulose; the defoamer is the organosilicon defoamer CF1829; the wetting dispersant is the hydrophobically modified ammonium salt dispersant Alcosperse747 and the wetting agent Ethylan1005; the mildew and algae preventer is OIT; and the thickener is the polyurethane thickener RM-8W.
[0091] Preparation steps: The same as the preparation method in Example 1, thereby preparing a reference water-based inorganic fire-retardant energy-storage luminous coating.
[0092] Comparative Example 3 Preparation of Reference Water-Based Inorganic Fire-Resistant Energy Storage Luminous Coating
[0093] The raw materials include: the same as those in comparative example 1, except that the luminescent material is the reference modified rare earth aluminate luminescent material DA1.
[0094] Preparation steps: The same as the preparation method in Example 1, thereby preparing a reference water-based inorganic fire-retardant energy-storage luminous coating.
[0095] Comparative Example 4 Preparation of Reference Water-Based Inorganic Fire-Proof Energy Storage Luminous Coating
[0096] The raw materials include: the same as comparative example 1, except that the luminescent material is the reference modified rare earth aluminate luminescent material DA2.
[0097] Preparation steps: The same as the preparation method in Example 1, thereby preparing a reference water-based inorganic fire-retardant energy-storage luminous coating.
[0098] Test Case
[0099] The performance of the water-based inorganic fire-retardant energy-storage luminous coatings prepared in the above examples and comparative examples was tested according to the following method, and the results are shown in Tables 1 and 2.
[0100] (1) The alkali resistance and water resistance of the coating shall be tested according to the method in JG / T 24-2018 "Synthetic resin emulsion sand-walled architectural coatings", the scrub resistance of the coating shall be tested according to the method in GB / T 9266-2009 "Determination of scrub resistance of architectural coatings", and the fire resistance level and smoke toxicity hazard level shall be determined according to the method in GB 8624-2012 "Classification of combustion behavior of building materials and products".
[0101] (2) Luminescence performance test: According to the method in JG / T 446-2014, the afterglow time of the light source (using D65 standard light source as the excitation light source, the intensity of D65 light source is 900 Lux) when irradiated for 10 min or 1 h was tested.
[0102] (3) Viscosity change after 15 days of hot storage: refer to the method in JG / T 24-2018 "Synthetic resin emulsion sand-walled architectural coatings". Put the coating into glass or plastic, seal it, and place it in a constant temperature box at (50±2)℃ for 15 days. Take it out and record the viscosity before and after hot storage.
[0103] (4) Initial drying anti-cracking performance and paint film board surface effect: The initial drying anti-cracking performance of the coating was tested according to the method in JG / T 24-2018 "Synthetic resin emulsion sand-walled architectural coatings". The coating film was prepared on black and white test cardboard using a film former with a gap of 150 μm. After the coating film was dried, the paint film board surface effect was determined by visual inspection and hand touch.
[0104] Table 1
[0105]
[0106] Table 2
[0107]
[0108]
[0109] It can be seen from the results of Table 1 that, compared with Comparative Examples 1 to 4, the water-based inorganic fire-retardant energy storage luminescent coatings provided by Examples 1 to 7 of the present invention have better initial drying anti-cracking performance, good paint film board effect and thermal storage stability, and have good luminescent performance and fireproof performance, and the smoke toxicity hazard classification can reach AQ1 safety level. It can be seen from the results of Example 1 and Comparative Example 1 that when the modified rare earth aluminate luminescent material is not used, the obtained coating is easy to crack during initial drying, the paint film board feels rough, the viscosity changes greatly after 15 days of thermal storage, and the thermal storage stability is poor. It can be seen from the results of Example 1 and Comparative Example 2 that when the amount of modified rare earth aluminate luminescent material is too much, although the luminescent performance of the obtained coating can be enhanced, it will cause cracking during the initial drying of the coating and the problem of rough feel of the paint film board. It can be seen from the results of Example 1 and Comparative Examples 3 and 4 that the rare earth aluminate luminescent material was not modified by a specific method, and the resulting coating was prone to cracking during initial drying, the paint film surface felt rough, and the viscosity changed greatly after 15 days of heat storage, and the heat storage stability was poor.
[0110] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A water-based inorganic fire-proof energy storage luminous paint, characterized in that: Based on the total mass of the water-based inorganic fireproof energy-storage luminescent coating, the water-based inorganic fireproof energy-storage luminescent coating contains 18.0-50.0wt% of water, 15.0-35.0wt% of inorganic silicate, 3.0-10.0wt% of inorganic hybrid resin, 25.0-40.0wt% of modified rare earth aluminate luminescent material, 0.1-0.6wt% of cellulose, and 0.2-3.6wt% of auxiliary agent; the modified rare earth aluminate luminescent material is obtained by modifying an unmodified rare earth aluminate luminescent material with an alkynyl compound, a vinyl-terminated polymethylsiloxane, and an alkylbenzene sulfonate.
2. The water-based inorganic fire-retardant energy storage luminous paint according to claim 1, characterized in that: The mass ratio of the unmodified rare earth aluminate luminescent material to the acetylenic compound, vinyl-terminated polymethylsiloxane and alkylbenzene sulfonate is 1:(0.002-0.004):(0.003-0.006):(0.003-0.006).
3. The water-based inorganic fire-retardant energy storage luminous paint according to claim 1, characterized in that: The unmodified rare earth aluminate luminescent material is selected from at least one of strontium aluminate, barium aluminate, calcium aluminate, europium aluminate, and manganese aluminate; Preferably, the alkynyl compound is selected from at least one of acetylene, 1-propyne, 2-propyne, 1-butyne, 2-butyne, 1-pentyne, 2-pentyne, and 3-methyl-1-butyne; Preferably, the number average molecular weight of the vinyl-terminated polymethylsiloxane is 200 to 400 g / mol; Preferably, the alkylbenzene sulfonate is selected from at least one of sodium dodecylbenzene sulfonate, potassium dodecylbenzene sulfonate, calcium dodecylbenzene sulfonate and triethanolamine dodecylbenzene sulfonate.
4. The water-based inorganic fire-retardant energy storage luminous paint according to claim 1, characterized in that: The modification reaction conditions include: temperature of 120-200°C and time of 3-5h; Preferably, the modification reaction is carried out in the presence of a solvent.
5. The water-based inorganic fire-retardant energy storage luminous paint according to claim 1, characterized in that: The particle size of the modified rare earth aluminate luminescent material is 25 to 75 μm.
6. The water-based inorganic fire-retardant energy storage luminous paint according to claim 1, characterized in that: The inorganic silicate is selected from at least one of potassium silicate, lithium silicate, sodium silicate and silica sol; Preferably, the auxiliary agent is selected from at least one of a defoaming agent, a wetting and dispersing agent, an anti-mildew and anti-algae agent, and a thickener.
7. The water-based inorganic fire-retardant energy storage luminous paint according to claim 6, characterized in that: Based on the total mass of the water-based inorganic fireproof energy-storage luminous paint, the content of the defoamer is 0.2-0.8wt%, the content of the wetting and dispersing agent is 0.3-1.0wt%, the content of the mildew and algae preventer is 0.2-1.0wt%, and the content of the thickener is 0.2-0.8wt%.
8. The water-based inorganic fire-retardant energy storage luminous paint according to claim 6, characterized in that: The wetting and dispersing agent is selected from at least one of amines, phosphates, carboxylates, polyacid homopolymers, and polyacid copolymers; Preferably, the mildew and algae preventer is selected from at least one of OIT, DCOIT, MIT, IPBC and ZnP; Preferably, the thickener is selected from at least one of a polyurethane thickener, an alkali swelling thickener and a bentonite thickener.
9. The method for preparing the water-based inorganic fire-proof energy storage luminous coating according to any one of claims 1 to 8, characterized in that: The preparation method comprises: mixing water, inorganic silicate, inorganic hybrid resin, modified rare earth aluminate luminescent material, cellulose and auxiliary agent in proportion to obtain water-based inorganic fireproof energy storage luminescent coating.
10. Use of the water-based inorganic fire-proof energy-storage luminous paint according to any one of claims 1 to 8 in tunnels and other building materials.